CURRENT DIAGNOSIS, PREVENTION AND TREATMENT OF DRY SOCKET: (literature review) - Hutor, N. S. (International Journal of Medicine and Medical Research, 2022)
Background. Tooth extraction is the most common surgical intervention in the outpatient practice of a dental surgeon. In most cases, bone wound healing is uncomplicated. However, in some patients the course of healing is complicated by acute inflammatory process of dry socket (alveolar osteitis), the frequency of which increases with increasing trauma of surgery. In dentally healthy patients with typical tooth extraction, dry socket occurs in 2.55%, with difficult – in 9.84%, with atypical extraction of the lower wisdom tooth – in 31.03% of cases. In the presence of diabetes, the incidence of dry socket with typical removal is much higher and according to various authors it is 9.7-13.5%. Objective. The aim of the research was to study the publications and their analysis on the current diagnosis, prevention and treatment of patients with dry socket. Methods. Scientific sources were the articles in world periodicals on dental surgery and therapy, microbiology as well as some electronic resources and patents. Results. At present, many techniques, methods, schemes, compositions for treatment of various forms of dry socket are established. Most often, antibacterial drugs or their combinations with other drugs are used. However, antibacterial drugs do not always have a pronounced anti-inflammatory effect due to the high resistance of the oral microflora. In these cases, contemporary drugs in the form of a composition with long-term antiseptic, anti-inflammatory and analgesic action are rational. Conclusions. The action of a Flupetsal composition, which contains antimicrobial and immunomodulatory drug flurenizide, was clinically proven for treatment of patients with dry socket; the properties of the available ingredients provide a high disinfectant effect, prevent development of inflammation in the tissues and its transition to purulence. A contemporary effective method of treating patients with dry socket is carried out according to the developed method.